2008
DOI: 10.12973/ejmste/75344
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Species Identification – A Prerequisite for Learning Biodiversity and Understanding Ecology

Abstract: Animal and plant species identification is often emphasized as a basic prerequisite for an understanding of ecology and training identification skills seems a worthwhile task in biology education. Such identification tasks could be embedded into hands-on, groupbased and self-determined learning: a) Teaching and learning should make use of a small selection of species (6-8) and b) these species should be embedded into learning about their natural and life history; c) different materials could be used for identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0
25

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(107 citation statements)
references
References 36 publications
0
82
0
25
Order By: Relevance
“…We noticed, as others have reported (Randler, 2008), that the transition from learning about, observing, studying, and holding captive animals in the classroom before going into the field helped many youth get comfortable with herpetology. For example, the aquaria, with lids, helped the youth closely examine the animals without touching them and then gradually get brave enough to hold them.…”
Section: Boundary Objectsmentioning
confidence: 59%
“…We noticed, as others have reported (Randler, 2008), that the transition from learning about, observing, studying, and holding captive animals in the classroom before going into the field helped many youth get comfortable with herpetology. For example, the aquaria, with lids, helped the youth closely examine the animals without touching them and then gradually get brave enough to hold them.…”
Section: Boundary Objectsmentioning
confidence: 59%
“…In reviewing literature on species identification, Randler (2008) found claims that many syllabi emphasise or require the use of scientific keys for identification, the argument being that they help students look more closely at detail (and are more scientifically precise). In contrast, when using books, students tend to focus on the illustrations alone (and the evidence from the study reported here suggests that the same is true of Internet-based visual resources, indeed some students compared NatureGate with working through pictures in a book).…”
Section: Discussionmentioning
confidence: 99%
“…However, modern biology curricula focus on aspects of genetics, ecology and evolution, and there is less coverage of systematics than in earlier times. Randler (2008) argues that the ability to identify species is important not only for understanding these branches of biology but also for a better understanding of biodiversity and issues about the environment and sustainability. Professional ecologists (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Randler (2008) believed that identifying animals and plants is a valuable task for understanding the environment and considered biodiversity an uncertain and complex structure. This complex and abstract structure typically needs to be transformed into small entities for purposes of learning and understanding.…”
Section: Transformative Learning For Community Volunteersmentioning
confidence: 99%
“…This complex and abstract structure typically needs to be transformed into small entities for purposes of learning and understanding. Randler (2008) also pointed out that, aside from its use with school students, this process is also applicable to ordinary citizens. Notably, the number of species to be identified in the learning process should not be excessive since too many can be confusing, and thus reduce the effectiveness of learning (Randler, 2008); the most appropriate number is between six and eight species (Randler & Bogner, 2006).…”
Section: Transformative Learning For Community Volunteersmentioning
confidence: 99%